1981
DOI: 10.1002/aheh.19810090204
|View full text |Cite
|
Sign up to set email alerts
|

Zur Beeinflussung von Planktonpopulationen durch Butonat, Trichlorfon und Dichlorvos

Abstract: Einf uhrungUntersuchungen zum Vorkommen und Verhalten von ausgewahlten phosphororganischen Pflanzenschutz-und Schadlingsbekampfungsniitteln (PSM) in1 Wasser haben zu dem Ergebnis gefuhrt, daIj Wirkstoffe iriit relativ kleiner Halbwertszeit, wie das z. B. unter den Bedingungen eutropher Oberflachengewasser fur Butonat, Trichlorfon und Dichlorvos der Pall ist, ausschlieBlich nach vorangegangenen YSMApplikationen im Nano-und Mikrogrammbereich pro Liter Untersuchungswasser analytisch nachweisbar sind (ACKERMA" et … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1981
1981
2004
2004

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Li and colleagues (1996) found that the application of 0.05 mg L −1 of trichlorfon into fishponds reduced the abundance of cladocerans but did not suppress the abundance of rotifers. Grahl, Horn and Hallebach (1981) reported that the application of 0.3–0.8 mg L −1 trichlorfon killed cladocerans and copepods, but increased the abundance of rotifers in fishponds. Similarly, Ludwig (1993) reported that the application of 0.25 mg L −1 of trichlorfon reduced the rotifer abundance and altered the successional pattern of crustacean zooplankton in fishponds.…”
Section: The Range Of Trichlorfon Concentrations (Mg L−1) Used In Tementioning
confidence: 99%
“…Li and colleagues (1996) found that the application of 0.05 mg L −1 of trichlorfon into fishponds reduced the abundance of cladocerans but did not suppress the abundance of rotifers. Grahl, Horn and Hallebach (1981) reported that the application of 0.3–0.8 mg L −1 trichlorfon killed cladocerans and copepods, but increased the abundance of rotifers in fishponds. Similarly, Ludwig (1993) reported that the application of 0.25 mg L −1 of trichlorfon reduced the rotifer abundance and altered the successional pattern of crustacean zooplankton in fishponds.…”
Section: The Range Of Trichlorfon Concentrations (Mg L−1) Used In Tementioning
confidence: 99%
“…Divers auteurs (Meles et al, 1977 ;Boyle, 1980 ;Papst & Boyer, 1980 ;Grahl et al, 1981 ;Huber & Gemes, 1981) ont note, soit dans des milieux naturels, soit dans milieux experimentaux, l'augmentation du taux de chlorophylle ou de la biomasse phytoplanctonique apres le traitement soit par des herbicides (linuron, 2,4-DDMA, butonat, trichlorfon), soit par des insecticides (abate, dursban, methoxychlore, dichlorvos) . Ces auteurs concluent tous que cet effet est lie a une diminution du broutage par le zooplancton tres sensible a ces produits .…”
Section: Chlortoluron N D J 1979unclassified